THE EFFECT OF WORK ENVIRONMENT AND TEACHER DIGITAL LITERACY ON THE QUALITY OF EDUCATION WITH TEACHER PERFORMANCE AS AN INTERVENING VARIABLE IN LOKHSUMAWE - Ahmad; Syaifuddin; Fajar Rezeki Ananda Lubis (Adisam Publisher, 2026)
The decline in the quality of education is largely caused by various factors, both internal and external. Therefore, an in-depth study is needed to find a solution to overcome this problem. Like this study will test whether there is an influence of the work environment and digital literacy of teachers on the quality of education with teacher performance as an intervening variable in Lokhsumawe. The collection of research data used a quantitative data approach with 150 samples in all State Senior High Schools (SMAN) in Lhoksumawe City. The results of the study showed that there was an influence of the Work Environment and Digital Literacy on teacher performance at Lhoksumawe City Senior High Schools. Furthermore, there was also an influence of the Work Environment, and Teacher Digital Literacy on the Quality of Education at Lhoksumawe City Senior High Schools. Likewise, there is an influence of Teacher Performance on the Quality of Education at Lhoksumawe City Senior High Schools, then there is an influence of the Work Environment and Digital Literacy on the Quality of Education through Teacher Performance at Lhoksumawe City Senior High Schools.